Diagnosis of the reality of the gap for the requirements of Business Continuity Management System According to International Standard (ISO 22301: 2012) in Midland Refineries Company (Daura Refinery) - الفيحان, ايثار عبدالهادي; عبدالباقي, سجى علي (Journal of Economics and Administrative Sciences, 2016)
Abstract:The current research included " Diagnosis of the reality of the gap for the requirements of Business Continuity Management System According to International Standard (ISO 22301: 2012) in Midland Refineries Company (Daura Refinery) " , for development of an administrative system for Business Continuity is considered a priority in the present day, and in the light of the organizations dependence on computers and information technology in work and communication with others . the international legitimacy (represented by the international organization for standardization (ISO)) remains the basis for matching and commitment , and the importance of the application of Business Continuity Management System According to International Standard (ISO 22301: 2012) In protecting organizations from business interruption risk and exposure to accidents and crises.Research problem is personified in the non- adoption of a management system for Business Continuity as provided by the standard (ISO 22301: 2012). Business stop after crisis and incidents which requires the existence of a system for the management of business continuity, which is central aim of the research. therefore research targeted evaluating between the Business Continuity Management System that currently exists in Daura Refinery ( sit of conducting the research ) and the Business Continuity Management System according to the international standard (ISO 22301:2012) by using examining checklist in order to diagnose non- conformity gaps with the international standard.The research introduced current gap evaluation and diagnosis for applying and documenting business continuity management system according to the international standard (ISO 22301:2012) in Daura Refinery , to conduct a comprehensive assessment of the level of performance of business continuity in the refinery, in order to understand and adoption these requirements as international standards , which help Refinery to get the (ISO) certificate . The research have been reached to inadequate documentation even absent ,in some activities of the studied Refinery , as a major reason for the gap .